2018
DOI: 10.1364/oe.26.017236
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-controlled multifrequency coherent perfect absorption in stereometamaterials

Abstract: We experimentally demonstrate polarization-controlled multifrequency coherent perfect absorption in stereometamaterials with twisted asymmetrically split rings. The coupling effects in stereometamaterials lead to the mode hybridization and thus multiple electric and magnetic resonances. The coherent perfect absorptions of electric and magnetic modes in stereometamaterials have been verified to be individually switched on/off by an interferometric effect of two counter-propagating coherent beams. The alternatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In these cases, metasurfaces must carry also magnetic surface currents, which requires the use of at least two parallel arrays or some volumetric particles [14]. However, coherent metasurfaces can produce these desired effects using a secondary illumination source, even if the metasurface sheet is negligibly thin and no magnetic current can be excited [15][16][17][18][19][20][21]. Space-modulated metasurface boundaries, realized as finite-size layers carrying both electric and magnetic surface currents, can behave as asymmetric absorbers [12,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, metasurfaces must carry also magnetic surface currents, which requires the use of at least two parallel arrays or some volumetric particles [14]. However, coherent metasurfaces can produce these desired effects using a secondary illumination source, even if the metasurface sheet is negligibly thin and no magnetic current can be excited [15][16][17][18][19][20][21]. Space-modulated metasurface boundaries, realized as finite-size layers carrying both electric and magnetic surface currents, can behave as asymmetric absorbers [12,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Since Landy et al firstly reported the concept of the perfect MMA consisting of two resonators coupled to the electric and magnetic fields separately to absorb the incident waves [7], the realizations of the high performance and multi-functional MMAs for various applications are always the important goals pursued by researchers [8,9]. Up to now, various MMAs, which are either multiple bands [10][11][12], polarization-insensitive [13,14] or polarization-sensitive [15,16], ultra-narrowband [17][18][19][20], and broadband [21], have been successfully realized to absorb EM waves across the whole spectrum from microwave to terahertz [22][23][24][25]. Chen proposed the interference theory to explain the physical mechanism of MMAs, an extremely broadband absorber based on destructive interference mechanism was demonstrated [26].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, a metasurface absorber in form of a lossy sheet can only absorb up to 50% of the incident power since the tangential electric field is continuos across the sheet. Nevertheless, coherent illumination of such sheets helps to reach 100% absorption [1][2][3][4][5][6]. However, physically, coherent perfect absorbers do not show additional advantages beyond their intended purpose of reducing reflections.…”
Section: Introductionmentioning
confidence: 99%